PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN IPS MATERI MASYARAKAT INDONESIA MASA PRAAKSARA, HINDU-BUDHA, DAN ISLAM PADA SISWA KELAS VII C SMPN 33 BANDAR LAMPUNG - Kartini, Kartini (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study is to describe improving social studies learning outcomes for students by applying the Think Pair Share learning model to social studies learning. The type of research is classroom action research. The subjects of this study were 32 students of class VIIC at SMPN 33 Bandar Lampung for the 2018/2019 academic year, consisting of 18 male students and 14 female students. Data collection techniques used test and non-test techniques. This classroom action research was conducted in 2 cycles, each consisting of 2 meetings. Each meeting consists of 4 stages, namely planning, implementing, observing, and reflecting. The results showed that application of the Think Pair Share Learning Model in social studies learning can improve social studies learning outcomes of Indonesian Society Material during the Praaksara, Hindu-Buddhist and Islamic periods of class VII SMPN 33 Bandar Lampung 2018/2019.